Incidental detection of colorectal lesions by FDG PET/CT scans in melanoma patients. Issue 11 (November 2017) - Young, Christopher J.; Zahid, Assad; Choy, Ian; Thompson, John F.; Saw, Robyn P.M.
Abstract: Background: Increased use of PET/CT scans in oncology patients has raised detection of Colorectal incidentalomas (CIs). The frequency and diagnostic outcomes of identifying these lesions in melanoma patients have not previously been studied. This studies primary objective was to determine the prevalence of CIs found on PET/CT scans in melanoma patients. The secondary objectives were to correlate the PET/CT findings with the pathology found at colonoscopy, and identify which patients were referred for colonoscopy. Methods: A retrospective analysis of patients identified from the prospectively collected research database of Melanoma Institute Australia. 2509 patients with melanoma underwent PET/CT scans between 2001 and 2013. The prevalence of CIs, the correlation of lesions, and the survival of patients who underwent colonoscopy versus patients who did not were analyzed. Results: The prevalence of CIs in melanoma patients who had PET/CT scans was 3.2%. Forty-five of the 81 (56%) patients with CIs underwent colonoscopy. Of these, premalignant or malignant disease was found in 58%. Patients with previous metastatic melanoma were significantly less likely to be referred for colonoscopy. Patients undergoing colonoscopy had significantly better survival, as did those without previous distant metastases before the CIs were found, and those without any metastases at the time the CIs were found. These factors were not significant on multivariate analysis. Conclusion: The prevalence of incidental colorectal lesions identified on PET/CT scans in melanoma patients was found to be equivalent to that in the general cancer population. Patients undergoing colonoscopy had better survival than those who did not.